Early and elongated epochs of planetesimal dynamo generation - Sanderson, HR; Bryson, JFJ; Nichols, CIO (Elsevier, 2024)
Accreting in the first few million years (Ma) of the Solar System, planetesimals record conditions in the protoplanetary disc and are the remnants of planetary formation processes. The meteorite paleomagnetic record carries key insights into the thermal history of planetesimals and their extent of differentiation. The current paradigm splits the meteorite paleomagnetic record into three magnetic field generation epochs: an early nebula field (≲5 Ma after CAI formation), followed by thermal dynamos (∼5–34 Ma after CAI formation), then a gap in dynamo generation, before the onset of core solidification and compositional dynamos. These epochs have been defined using current thermal evolution and dynamo generation models of planetesimals. Here, we demonstrate these epochs are not as distinct as previously thought based on refined thermal evolution models that include more realistic parametrisations for mantle convection, non-eutectic core solidification, and radiogenic 60Fe in the core. We find thermal dynamos can start earlier and last longer. Inclusion of appreciable 60Fe in the core brings forward the onset of dynamo generation to ∼1–2 Ma after CAI formation, which overlaps with the existence of the nebula field. The second epoch of dynamo generation begins prior to the onset of core solidification this epoch is not purely compositionally driven. Planetesimal radius is the dominant control on the strength and duration of dynamo generation, and the choice of reference viscosity can widen the gap between epochs of dynamo generation from 0–200 Ma. Overall, variations in planetesimal properties lead to more variable timings of different planetesimal magnetic field generation mechanisms than previously thought. This alters the information we can glean from the meteorite paleomagnetic record about the early Solar System. Evidence for the nebula field requires more careful interpretation, and late paleomagnetic remanences, for example in the pallasites, may not be evidence for planetesimal core solidification.